2015
DOI: 10.9778/cmajo.20140044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pediatric palliative care programs on health care resource utilization and costs among children with life-threatening conditions: a systematic review of comparative studies

Abstract: P ediatric palliative care can be summarized as "an active and total approach to care focused on the enhancement of quality of life for the children with life-threatening conditions and support for the family".1 A life-threatening condition is a condition with no established cure, or for which available treatment has not succeeded, and survival to full adulthood is unlikely. Children requiring, but not enrolled in, a pediatric palliative care program (PPCP) access usual care often through uncoordinated acute c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…The authors reported no conclusive findings due to conflicting results on cost of care and an overall trend of reduction in length of stay (19). The cost decrease we find in this study, therefore, is consistent with some studies(20-23) but inconsistent with others, including a more M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 58%
“…The authors reported no conclusive findings due to conflicting results on cost of care and an overall trend of reduction in length of stay (19). The cost decrease we find in this study, therefore, is consistent with some studies(20-23) but inconsistent with others, including a more M A N U S C R I P T…”
Section: Discussionsupporting
confidence: 58%
“…Priorities for CPC research generally are varied, with research in HICs focusing on issues such as service evaluation,50–52 decision making,46 53 the impact of educational programmes,54 55 telehealth,56 57 preferred place of death,58 resource utilisation and costs,59 60 pain management,40 61 perinatal palliative care,62 screening for palliative care,63 64 and quality-of-life measures 65…”
Section: Status Of the Sciencementioning
confidence: 99%
“…28 However, a recent systematic review found conflicting results with 6 of 8 included studies indicating reduced overall costs when care was provided by a PPC team, but 2 studies finding an increase in costs. 29 Most included studies, plus a more recent analysis of costs associated with specialist PPC services, focused only on hospital-based costs rather than including costs that may have shifted to other settings, such as home care and hospice. 29,30 Because of universal health care coverage in Canada, we were able to track expenditures across multiple sectors, including home care; however, the costs associated with care in a freestanding hospice paid through philanthropic support were not included in our analysis.…”
Section: Tablementioning
confidence: 99%
“…29 Most included studies, plus a more recent analysis of costs associated with specialist PPC services, focused only on hospital-based costs rather than including costs that may have shifted to other settings, such as home care and hospice. 29,30 Because of universal health care coverage in Canada, we were able to track expenditures across multiple sectors, including home care; however, the costs associated with care in a freestanding hospice paid through philanthropic support were not included in our analysis. Unfortunately, we were also unable to determine which children received specialized PPC services due to nonspecific billing codes used by these teams.…”
Section: Tablementioning
confidence: 99%